The influence of social value orientation and group relations on fairness norms enforcement - Zhang, Zhen; Qi, Chunhui; Zhao, Guoxiang (Frontiers in Psychology, 2025)
Fairness norm enforcement represents a defining characteristic of human societies and is significantly influenced by group dynamics. However, the direction in which group relations influence the fairness norms enforcement remains controversial, and the underlying mechanism by which social value orientation modulates this effect has not yet been examined. A mixed experimental design with 2 (social value orientation: pro-socials vs. pro-selves) × 2 (group relationship: in-group vs. out-group) × 3 (proposal size: 5:5, 3:7, and 1:9) was employed to examine the impact of social value orientation and group relationship on the fairness norms enforcement during group resource allocation scenarios using a single anonymous ultimatum game. The results revealed that pro-socials were more likely to accept unfair distribution offers when interacting with in-group members compared to out-group members. However, no significant interaction effect between group relationship and proposal size on pro-selves’ acceptance rates was detected. Moreover, pro-selves responded significantly faster to the extremely unfair offers (1:9) when dealing with out-group members, whereas pro-socials exhibited shorter response times when interacting with in-group members. Responses to the other two distribution offers (3:7 and 5:5) were not significantly affected by either social value orientation or group relationship. Notably, for the 3:7 offers, pro-socials demonstrated higher in-group favoritism scores than pro-selves, while no such differences were observed for the 5:5 and 1:9 offers. These findings indicate that social value orientation and group relationship can jointly influence individuals’ normative responses to unfair distribution schemes.